(untitled) (Public Sector Economics - submission site, 2024)
During the Covid-19 pandemic, the debate on monetary financing was reignited and several economists called for governments to borrow from their central banks to finance larger deficits. Sub-Saharan Africa provides useful insights into this debate since it is a region where “fiscal dominance” has long been widespread. We find that fiscal dominance is stronger during periods of pressure on public finances, particularly when alternative financing options are limited. We also find that central bank financing of government does have an inflationary impact through the exchange rate channel. Numerical legal limits on central bank financing can be an effective way to mitigate the risks, even if they are not always binding.